Pengaruh Profitabilitas, Ukuran Perusahaan, Keputusan Investasi, Dan Kebijakan Hutang Terhadap Nilai Perusahaan(Studi pada Perusahaan Manufaktur yang terdaftar di Bursa efek Indonesia Periode 2010-2014) - Nurhayati, Kurnia Fadilah, Dr. Triyono, SE, M.Si (2016)
The value of the company is an investor perception of the level of success of the company associated with the stock price. The company's value in this study was measured with Price Book Value. This study aimed to analyze the effect of profitability, company size, investment decisions, and policies on the company's debt to the value of companies listed in Indonesia Stock Exchange 2010-2014. The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2010-2014. The method of collecting samples by purposive sampling according to criteria that have been determined. The number of samples collected as many as 65 companies. The data were analyzed first using classic assumption test. To test the hypothesis using multiple linear regression analysis. The results showed that the coefficient of determination obtained a value of 0.222%, which means that 22.2% of the value of companies affected by profitability, company size, investment decisions, and debt policy, while 77.8% are influenced by other factors beyond this variable. F test results showed acceptable F count 5.569 at significant level of 5%. The results of hypothesis test (t test) showed that partially profitability, company size, and investment decisions are positive and significant effect on a significant level of 5%. This suggests that profitability, company size, and investment decisions can affect both the poor value of the manufacturing company. While the debt policy has no effect on the value of the company.